Pengaruh Program Pelatihan UMKM dalam Pemanfaatan Teknologi Digital terhadap Produktivitas UMKM Kerupuk Rajungan Desa Sukajaya, Cilamaya Kulon - Anggraeni, Silvi; Sungkono, Sungkono; Retnosary, Rieke (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
Based on observations, it is known that the main problem is the lack of a thorough understanding of sales technology that can increase the productivity of the crab crackers. This research intends to see if there is an effect of training on the utilization of digital technology on the productivity of umkm crab crackers in Sukajaya Village, Cilamaya Kulon. The total sample in the research was 93 people. Using quantitative method with simple linear regression analysis. According to observations, it is known that the case in the research is the lack of skills and understanding of digital technology that can increase productivity. based on the results of the simple linear regression test for productivity of 37.587%, based on the research conclusion shows that work learning has an absolute impact on the sales productivity of crab cracker MSMEs in Sukajaya Village, Cilamaya Kulon. Based on the results of the coefficient of determination (R2) value of 0.298, this case states that job training has an impact on productivity in the crab cracker SMEs of Sukajaya Village, Cilamaya Kulon Cilamaya Kulon as much as 29.8% while as much as 70.2% is influenced by other causes that are not tested. The conclusion of the research shows that training has an absolute effect on productivity.